Heterogeneous distributed problem-solving involving visual objects as boundary objects - Harvey, Francis (Frontiers in Communication, 2024)
Communication involving visualizations in science and applications involves or even requires coordination. Much visualization research focuses on tasks in research or applications and provides valuable insights that help improve these modes and means of communication. That focus and resulting benefits makes a reduction to tasks or defined goals seem amenable for a more thorough consideration of social and cultural aspects. This contribution to the focus topic Insights in Visual Communication suggests that the boundary object concept can greatly help deepen considerations of social and cultural heterogeneity and adds insights and perspectives to better consider social and cultural aspects of visual communication. The theoretical concept of boundary objects, originating in heterogeneous distributed problem solving research, offer a pragmatic basis for enhancing visual communication to improve meaning production. The overarching issue for developing this direction in visual communication can be formulated through a broad question: In heterogeneous situations, how can research enhance communication involving visual objects for problem solving through a consideration of social and cultural aspects? I consider an example of cooperative design of maps to show how research can benefit from a consideration of boundary objects. The example highlights a cooperative mode of visual communication used in decision making involving both explicit and implicit goals and aspects from a cognitive perspective. The potential for improvements and better solutions in visual communication can benefit from a stronger consideration of the boundary objects concept.